The effect of a physical activity program using whatsApp on adolescents' exercise behavior - EROL, SAİME (My University, 2022)
This study aims to demonstrate the effect of a transtheoretical model (TTM)-based physical activity program on the exercise behavior of adolescents using WhatsApp. The study was conducted with high school students (N = 185) in a pre-/posttest, quasi-experimental design. TTM-based text messages were sent to the intervention group (n = 95) over WhatsApp every day for 8 weeks. The intervention group demonstrated more statistically significant progression in the exercising stages of change compared to the control group (n = 90) (chi(2) = 20.10; p = .00). It was also found that this group had a higher exercising self-efficacy score (t = 2.647; p = .009) and a higher physical activity total metabolic equivalent of task score (Z = -3.521; p = .000). There was no significant difference in BMI and perception of pros and cons (p > .05). The program was found to be effective in terms of recording progress in the exercising stages of change, increasing exercising self-efficacy, and maintaining a physical activity program.
Keywords: Tıp; Hemşirelik; Sağlık Bilimleri; Medicine; Nursing; Health Sciences; HEMŞİRELİK; Klinik Tıp; Klinik Tıp (MED); NURSING; CLINICAL MEDICINE; Clinical Medicine (MED); Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; physical activity; adolescent; transtheoretical model; WhatsApp; exercising; TRANSTHEORETICAL MODEL; SELF-EFFICACY; INTERVENTION; CHILDREN